The promotion of digital agency in future educator training - Rigo, Daiana (2023)
The research aimed to understand how students, future teachers in the Teaching and Bachelor's programs in Early Education, perceived themselves in relation to digital agency, i.e., the ability to adapt to a digital world, after participating in an educational experience mediated by the use of Empowerment and Participation Technologies, specifically quick response codes. A qualitative study was conducted, involving university students from Argentina (n=22), selected through convenience sampling, using a questionnaire as a data collection instrument. The results show that students value the importance of creating agential contexts for the development of digital competence, responsibility, and confidence, which, in turn, can promote reflections on constructed professional identities, as well as rethink ideas and beliefs regarding technologies, empowering and innovating their future teaching practices.